AIDS defining disease: Disseminated cryptococcosis - Roshan Anupama; Janaki C; Selvi G; Parveen B; Gomathy N (Wolters Kluwer Medknow Publications, 2006)
Disseminated cryptococcosis is one of the acquired immune deficiency syndrome defining criteria and the most common cause of life threatening meningitis. Disseminated lesions in the skin manifest as papules or nodules that mimic molluscum contagiosum (MC). We report here a human immunodeficiency virus positive patient who presented with MC like lesions. Disseminated cryptococcosis was confirmed by India ink preparation and histopathology. The condition of the patient improved with amphotercin B.